Pshycotherapeutic Adaptaations for Older Adults: A Review of the S State of the Art (Jóvenes en la Ciencia, 2026)
The objective of this review is to synthesize the evidence on psychotherapeutic adaptations in older adults, identifying conceptual gaps and methodological limitations. Forty studies published between 1992 and 2024 were reviewed in international databases and gray literature, comprising theses, technical reports, and various academic documents not officially published. The results show a predominance of cognitive-behavioral therapy (CBT), while humanistic and integrative approaches appear to a lesser extent. The most common adaptations include simplification of language, reduction of tasks, use of visual aids, and adjustments in the duration of sessions, with effectiveness in reducing depression and anxiety and improving well-being. Humanistic approaches provide existential validation and biographical reframing, and integrative approaches offer flexibility and community relevance. Methodological limitations persist (small samples, scarcity of controlled trials, and lack of follow-up), as well as geographical bias, given that most studies come from high-income countries. In conclusion, adaptations are effective and necessary, but it is essential to move toward a comprehensive theoretical framework and develop clinical manuals, specialized training, and multicenter studies to ensure culturally relevant and scalable interventions.